Pengaruh Konsentrasi Pupuk Organik Cair Kulit Pisang Kepok terhadap Pertumbuhan dan Hasil Tanaman Bayam Merah (Amaranthus tricolor L.) - Natania, Inggrid Olivia; Pradnyawathi, Ni Luh Made; Astawa, I Nyoman Gede (Fakultas Pertanian Universitas Udayana, 2024)
Effect of Concentration of Kepok Banana Peel Liquid Organic Fertilizer on Growth and Yield of Red Spinach (Amaranthus tricolor L.). This study aims to determine the effect and the best concentration of kepok banana peel liquid organic fertilizer which gave the highest growth and yield for red spinach (Amaranthus tricolor L.). This study used a completely randomized design (CRD) with 6 treatments, namely 0, 10, 20, 30, 40 and 50 ml/l with 4 repetitions. The research was conducted in the greenhouse of the Experimental Garden of the Faculty of Agriculture and Agronomy and Horticulture Laboratory, Udayana University from November 2022-February 2023. The application of fertilizer had an effect and a concentration of 50 ml/l was the best concentration which gave the highest yield which increased plant height 29 dap 139% (19.48 cm), number of leaves 29 dap 358.06% (35.50 strands), leaf area 875.30% ( 39.50 cm2), root length 154.39% (26.33 cm), fresh weight of plant tops 407.83% (26.56 g), oven dry weight of tops of plants 493.54% (3, 68 g), root fresh weight 389.7% (12.83 g), root oven dry weight 103.22% (1.26 g), root shoot ratio 168.31% (2.71) and leaf chlorophyll content 220 .85% (25.38 units) compared to control (8.15 cm, 7.75 strands, 4.05 cm2, 10.35 cm, 5.23 g, 0.62 g, 2, 62 g, 0.62 g, 1.01 and 7.91 units).